Critical thinking development technology: theoretical basis and its application in secondary school (to teaching the russian language) - Shtyrlina, Ekaterina Gennadievna; Kazantseva, Aida Marsovna; Hasan, Izanloo (Universidade Estadual Paulista, 2021)
The paper presents a modern pedagogical technology for the critical thinking development, aimed at forming the pupils' ability to analyze facts, phenomena, and processes from the standpoint of logic in their relationship and interdependence. It reveals the specifics of critical thinking development technology, provides a description of the methodology for critical thinking development using the example of teaching the Russian language at high school: the stages of the educational process (challenge, comprehension, reflection), techniques and methods of this technology, examples of their application and advantages of use. In course of the study, the authors conclude that the critical thinking development technology is implemented through the interactive inclusion of students in the educational space through a specific organization of the educational process based on three main stages and a system of teaching methods that consistently implement the tasks at each stage. The critical thinking development technology activates the pupils’ mental and speech activity and contributes to their active involvement in the educational and cognitive process. The study is based on the methods of observation, analysis, synthesis, description, comparison, and generalization.